Exponential Stabilization of Impulsive Switched Systems with Time Delays Using Guaranteed Cost Control - Xie, X.; Xu, Honglei; Zhang, R. (Hindawi Publishing Corporation, 2014)
This paper investigates the stabilization problem for impulsive switched systems with time delays. First, exponential stability criteria of the delayed impulsive switched systems are established by use of the Lyapunov-Krasovskii functional method. Based on these results, sufficient conditions for the existence of a guaranteed cost control are also given. Subject to these sufficient conditions, the closed-loop impulsive switched system under the guaranteed cost control law will be exponentially stable with a guaranteed cost value.